2006
DOI: 10.1051/rnd:2006044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silage type and concentrate level on conjugated linoleic acids, trans-C18:1 isomers and fat content in milk from dairy cows

Abstract: -The objective of the study was to examine how the fatty acid composition of milk especially concentrations of conjugated linoleic acids (CLA) and trans-C18:1 isomers and milk fat percentage were affected by silage type and concentrate level. Forty dairy cows were blocked and randomly assigned to one of four diets in a 2 × 2 factorial arrangement of treatments and a six week experimental period. Treatments were total mixed rations with maize (M) or grass (G) silage differing in polyunsaturated fatty acid (PUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 24 publications
8
45
2
1
Order By: Relevance
“…Inclusion of MS in the diet had no effect on milk fat content. Typically, increases in starch intake coupled with decreases in NDF ingestion are associated with a reduction in milk fat (Lock and Shingfield, 2004;Nielsen et al, 2006). A lack of effect on milk fat concentrations in this experiment may reflect a higher intake of NDF on MS-containing diets, in spite of this forage containing lower amounts of this constituent than GS.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Inclusion of MS in the diet had no effect on milk fat content. Typically, increases in starch intake coupled with decreases in NDF ingestion are associated with a reduction in milk fat (Lock and Shingfield, 2004;Nielsen et al, 2006). A lack of effect on milk fat concentrations in this experiment may reflect a higher intake of NDF on MS-containing diets, in spite of this forage containing lower amounts of this constituent than GS.…”
Section: Discussionmentioning
confidence: 80%
“…Kalscheur et al (1997) found that increasing the amount of dietary readily digestible carbohydrates caused an increase in certain milk trans 18:1. More specifically, studies have also found that complete replacement of GS with MS in the diet increases milk trans-10 18:1 concentrations (Shingfield et al, 2005;Ferlay et al, 2006;Nielsen et al, 2006). The effects of ruminant-derived trans FA on human health have yet to be fully clarified -the isomer profile of ruminant products is different from that of industrial trans FA.…”
Section: --mentioning
confidence: 99%
See 3 more Smart Citations